Pertumbuhan Tanaman Nyamplung sampai umur 4 (empat) tahun pada tiga pola tanam dan dosis pupuk di lahan Pantai Berpasir Pangandaran, Jawa Barat - Aditya Hani; Encep Rachman (Jurnal Penelitian Kehutanan Wallacea, 2016)
Nyamplung (Calophyllum inophyllum L.) is one of the new alternatives of biofuels materials in the world. Hitherto, the information on the cultivation and processing techniques is very limited. This study aims to find out the growth of nyamplung on some cropping patterns on sandy beach Pangandaran in 4 (four) years. The experimental design used in this study was split plot design. The main plots were cropping pattern: agroforestry nyamplung, nyamplung monoculture and nyamplung + pandanus, and the subplot were fertilizer doses: (1) no fertilizer (control), (2) 5 kg of organic fertilizer + 100 gr/plant NPK and (3) 10 kg of organic fertilizer + 200 gr/plant of NPK fertilizer. Each combination treatment consists of 25 plants that were repeated 3 times , so that the total number of plants observed were 675 plants. The growth parameters observed: survival rate, height, diameters and number of branches of plant until 4 years. The results of this study showed that the interaction of treatments were statistically not significant. The growth of the plants was significantly affected by cropping pattern and fertilization. The Agroforestry pattern produces the highest survival rate and growth that is 97.33% with an average height of 220 cm and an average diameter of 5.08 cm. Recommended fertilizer doses are 5 kg of organic fertilizer for base and 100 grams of advanced fertilizer NPK twice a year.